2001
DOI: 10.1103/revmodphys.73.203
|View full text |Cite
|
Sign up to set email alerts
|

Resonant inelastic x-ray scattering spectra for electrons in solids

Abstract: Resonant inelastic x-ray scattering (RIXS) has recently been a subject of remarkable progress due to the advent of high-brilliance synchrotron radiation sources. The authors present a review of both experimental and theoretical investigations of electrons in solids using this second-order optical process, in which there is coherent absorption and emission of x rays at resonance with electronic excitations. The review starts with some of the fundamental aspects of RIXS, after which are presented typical experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
627
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 782 publications
(635 citation statements)
references
References 207 publications
(208 reference statements)
7
627
1
Order By: Relevance
“…However, it was later suggested that PFY spectra cannot be viewed as genuine LBS-XAFS 16,17 (although for wide-band materials, where core-electron interactions are small, they can be a good approximation to LBS-XAFS). 6,16,18 Partially because of this indication, there were very few reports on succeeding PFY measurements. 19 An alternative method to obtain LBS-XAFS by using RIXS has been theoretically suggested by Tulkki and Åberg, 20 even before the proposition of the PFY spectroscopy (at 1982).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, it was later suggested that PFY spectra cannot be viewed as genuine LBS-XAFS 16,17 (although for wide-band materials, where core-electron interactions are small, they can be a good approximation to LBS-XAFS). 6,16,18 Partially because of this indication, there were very few reports on succeeding PFY measurements. 19 An alternative method to obtain LBS-XAFS by using RIXS has been theoretically suggested by Tulkki and Åberg, 20 even before the proposition of the PFY spectroscopy (at 1982).…”
mentioning
confidence: 99%
“…10 Here, the ground state is the initial state, 1s-excited state (same as the final state of absorption) is the intermediate state, and the hole in the intermediate state is filled by an electron in the 2p state, resulting in the emission of a photon with energy w2 (in atomic unit). This resonant process is described by the well-known Kramers-Heisenberg equation, 3,6,7,12 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The measured emission or absorption spectrum can then be interpreted in terms of the density of occupied valence band or unoccupied conduction band states, respectively. 7,8 Dipole selection rules ()l ± 1) govern the optical transition to or from the core-level, 7 and in the present case N K-edge XES and XAS measurements yield information on the N 2p PDOS. Unlike photoemission spectroscopy, these techniques are relatively insensitive to the quality of the sample surface and atomic cleaning is not necessary.…”
mentioning
confidence: 99%